Pengaruh Implementasi Artificial Intelligence terhadap Efektivitas Pengambilan Keputusan Manajerial pada Perusahaan Retail di Indonesia - Nabila Putri Rahmadani; Siti Fatimah; Theresa Windy Gumarus (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of artificial intelligence (AI) technology has fundamentally changed how organizations manage operations and make decisions. This study aims to analyze the influence of AI implementation on the effectiveness of managerial decision-making in Indonesian retail companies. Using a quantitative approach with a survey method, data were collected from 120 managers working at modern retail companies (Indomaret, Alfamart, Transmart, and Hypermart) in five major cities in Indonesia. Data analysis used multiple linear regression with classical assumption tests. The results showed that AI implementation dimensions—namely predictive analytics, inventory management systems, and customer behavioral AI—had a significant and positive effect on the effectiveness of managerial decision-making with a coefficient of determination (R²) of 0.712, meaning AI implementation can explain 71.2% of the variation in managerial decision-making effectiveness. The predictive analytics dimension had the strongest influence (β = 0.412, p < 0.001), followed by inventory management systems (β = 0.298, p < 0.001) and customer behavioral AI (β = 0.231, p < 0.01). These findings confirm that companies that have invested in AI infrastructure show significantly better decision quality, decision speed, and decision accuracy compared to companies that have not adopted AI. The study recommends that retail managers in Indonesia adopt AI gradually, with an emphasis on employee training and organizational change management.